2019
DOI: 10.1097/ncc.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based and Culturally Aligned Training Program on Breast and Cervical Cancer Prevention for South Asian Community Health Workers

Abstract: The theoretical framework of our CHW training program and the incorporated cultural components could be useful for the development of future programs for training South Asian CHWs in delivering interventions on cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Therefore, nurses should actively communicate with patients, especially at the beginning of rehabilitation. 17 19 The WeChat platform and telephone follow-up activities could be used to publicize disease knowledge so that patients can obtain correct information about disease rehabilitation and improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nurses should actively communicate with patients, especially at the beginning of rehabilitation. 17 19 The WeChat platform and telephone follow-up activities could be used to publicize disease knowledge so that patients can obtain correct information about disease rehabilitation and improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…CHWs can also assist South Asian ethnic minorities in scheduling cancer screening appointments. Our previous study demonstrated the positive effect of a CHW training program in enhancing CHW competence in increasing community peer knowledge of cervical cancer and self-efficacy in cervical cancer screening utilization [15]. As training South Asian CHWs within the local community is feasible, we speculate that the innovative approach of combining multimedia and CHWs in intervention delivery can enhance knowledge of cervical cancer screening among participants.…”
Section: Introductionmentioning
confidence: 90%
“…Within two weeks following the collection of the socio-demographics and baseline data upon subject recruitment, the CHWs directly contacted the participants to inform them of their schedule and venue for the intervention. The evidence-based multimedia educational intervention lasted for three months and was developed on the basis of the training program for CHWs developed by the project team [15] and recommendations from systematic reviews [11,12,13]. The intervention consisted of two parts: (1) a 30-min multimedia educational program presented using a structured PowerPoint slide with a video clip aiming to augment knowledge of cervical cancer and its prevention; (2) a monthly telephone follow-up once a month for three months and the provision of navigation assistance in accessing screening services.…”
Section: Methodsmentioning
confidence: 99%
“…A package of training materials was developed based on the existing literature and comments from the expert panel. The training program for the CHWs was examined in a previous feasibility study and shown to enhance participants’ knowledge of cancer, self-efficacy, and competence in working as CHWs [27]. The training of CHWs by the research team would require 14 h. Training will consist of seven sessions that cover the following: information about cervical cancer and screening; resources and access to screening tests; beliefs, myths, and misconceptions about cancer and cancer screening; barriers to cancer screening; facilitators and strategies to overcome such possible barriers; communication and problem-solving skills; and navigation support.…”
Section: Methodsmentioning
confidence: 99%
“…The trained CHW will deliver two 30-min health talks using a PowerPoint presentation on the following topics: definition of cervical cancer and risk factors, signs, and symptoms of cervical cancer; myths and misconceptions about cervical cancer; preventive measures for cervical cancer; and available preventive measures and service providers in Hong Kong [27]. Participants will then be asked to watch a 4-min video clip to reinforce the knowledge gained.…”
Section: Methodsmentioning
confidence: 99%